Mutual life, limited Islamic banking, alternative currencies, lateral reason - Maurer, Bill (Princeton University Press, 2005)
Based on fieldwork among Islamic bankers globally, this book questions the equivalence between money and ethnography and asks whether money can ever be adequate to the value backing it.